2015
DOI: 10.1007/s00221-015-4431-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the spatial and temporal modulation of visuotactile interactions in older adults

Abstract: Previous research has shown that spatially and temporally disparate multisensory events are more likely to interact for older adults. For visuotactile interactions, this suggests that the representation of peripersonal space is expanded and temporal perception within this space is less precise. Previously, visuotactile space has been found to expand horizontally into the opposite hemispace, and here we sought to replicate and extend this by exploring both horizontal and vertical space from the hand. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Given the age‐related alterations in sensory and cognitive processing, one would also expect aging to be associated with major declines in multisensory perception. Yet, studies have shown that although older adults exhibit in general worse performance as compared to their young counterparts (e.g., slower reaction times), they show greater multisensory gains for different sensory combinations, including audiovisual, visual‐somatosensory, and audio‐somatosensory stimulus pairs . The greater multisensory gains observed in older adults have been replicated in paradigms differing in terms of their attentional demands and the tasks employed, such as simple reaction, discrimination, saccadic reaction time, and temporal perception tasks, thus pointing to a robust age‐dependent facilitative effect of multisensory processing on behavioral performance.…”
Section: Multisensory Processing In Old Age: Current Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the age‐related alterations in sensory and cognitive processing, one would also expect aging to be associated with major declines in multisensory perception. Yet, studies have shown that although older adults exhibit in general worse performance as compared to their young counterparts (e.g., slower reaction times), they show greater multisensory gains for different sensory combinations, including audiovisual, visual‐somatosensory, and audio‐somatosensory stimulus pairs . The greater multisensory gains observed in older adults have been replicated in paradigms differing in terms of their attentional demands and the tasks employed, such as simple reaction, discrimination, saccadic reaction time, and temporal perception tasks, thus pointing to a robust age‐dependent facilitative effect of multisensory processing on behavioral performance.…”
Section: Multisensory Processing In Old Age: Current Statusmentioning
confidence: 99%
“…The multisensory enhancements observed in healthy aging also entail older adults’ inclination to integrate all information available due to the wider temporal windows of integration and the inefficient weighting of sensory inputs. This tendency has been found to affect performance when part of the sensory information needs to be ignored (e.g., irrelevant information) and has been systematically linked to age‐related deviations from normal balance and gait, increased susceptibility to audiovisual illusions (i.e., decreased accuracy), poorer spatial working memory and poorer functional mobility, and altered decision making when inferring event causality . For example, fall‐prone older adults exhibit a wider window of integration and increased susceptibility (i.e., decreased accuracy) to audiovisual illusions as compared to those with no history of falling .…”
Section: Exploiting the Benefits Of Multisensory Processing For Succementioning
confidence: 99%
See 1 more Smart Citation
“…Stevenson and colleagues (2012) have also shown individual differences in MSI in non-RT based measures, even in a relatively more homogenous young adult group. Recent experiments within our lab have attempted to reduce this within and between group variability by initially constraining individual unisensory performance, thus enabling the influence of multisensory stimulation to be more easily observed (Poole et al, 2015a(Poole et al, , 2015bCouth, Gowen and Poliakoff, 2016). Similarly, there are other studies which have used different experimental approaches and models of multisensory processing which have demonstrated age-related differences, such as differences in sensory (re)weighting using (e.g.…”
Section: Solutions and Alternatives For Estimating Enhanced Integrationmentioning
confidence: 99%
“…vision) when the task requires participants to attend to-and make a judgement about-a single modality (e.g. touch), and so information from different sensory modalities may be more readily combined (Poliakoff, Ashworth, et al, 2006;Poliakoff, Shore, et al, 2006;Couth, Gowen and Poliakoff, 2016). Whichever the explanation, it has been demonstrated that older adults show enhanced integration even in a simple reaction time task (Peiffer et al, 2007), thus it seems likely that this effect emerges early at the level of signal detection, prior to any higher-level processes which may be affected by general cognitive slowing in ageing (cf.…”
Section: Introductionmentioning
confidence: 99%